Original paperTaxcor for the prevention of restenosis. Polish multicentre observational study to assess the efficacy and safety of the Genius TAXCOR I stent - Gil, Robert J.; Zasada, Wojciech; Dziewierz, Artur; Partyka, Łukasz; Zarębiński, Maciej; Wilczek, Krzysztof; Dudek, Dariusz; Buszman, Paweł; Lesiak, Maciej; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Background: The Taxcor PL registry was a multicentre, phase IV open clinical trial, in which there participated 10 academic centres in Poland. Its aim was to assess the safety and effectiveness of the stent Genius TAXCOR I (Eurocor GmbH, Germany) at a dose of 1 μg/mm 2 of paclitaxel, implanted during PCI with elective or urgent indications. Material and methods: Patients who entered the study were a group of patients qualified for PCI, based on clinical symptoms and provocative tests, in whom coronary angiography confirmed the presence of significant stenosis (length up to 25 mm) in the coronary arteries. Implantation procedure, peri- and postoperative procedure were in accordance with guidelines and local practice. The study protocol did not interfere with standard treatment for patients with a diagnosis of ischaemic heart disease. The total number of patients studied in the Taxcor PL registry is 100 people recruited in 10 centres in Poland. Results: Data were collected during the study on 100 PCIs (110 treated lesions). Average duration of PCI was 43 min (SD 24). Mean diameter of the implanted stent was 3.17 mm (SD 0.36) and the average length of 20.5 mm (SD 5.82). The mean time of hospitalization of patients enrolled in the study was 2.5 days (SD 3.4). During hospitalization, 2 patients experienced myocardial infarction which was the result of side branch closure during PCI. Three patients had a haematoma at the puncture site, which did not require surgical intervention and transfusion of blood products. During percutaneous coronary intervention also three cases of distal dissection were reported (type B, C and D). There were no other adverse events. In one-month follow-up one of the patients had a planned PCI procedure performed in another vessel than previously treated, which was the next stage of coronary revascularization. Similarly, in the 3-month follow-up one of the patients needed to undergo a PCI procedure on a vessel untreated with Taxcor. In the 6-month follow-up (3-6 months) one patient died – he was hospitalized with a diagnosis of malignant tumour and the gastrointestinal tract and operated on at the surgical ward (hemicolectomy); after 2 months of hospitalization, he died due to multiorgan failure. Five patients had a second percutaneous coronary intervention in other vessels than at the time of study enrolment. At 12-month follow-up (6-12 months) two patients had a second PCI procedure performed, including one in a vessel treated at the time of enrolment. Ineffectiveness of supply target vessel (called target vessel failure, TVF) occurred in three patients (death from coronary causes – 0, MI – 2, target vessel revascularization (TVR – PCI or CABG) during the 12-month observation period – 1. Conclusions : Taxcor PL registry results showed that the stent Genius Taxcor I is safe to use and provides satisfactory results in short- and long-term observation, in comparison with other commercially available coronary stent systems.